Design of PID controllers for dead–time systems using hybrid biogeography based optimisation. (27th November 2012) - Kanthaswamy, G.; Jerome, Jovitha
This paper introduces the application of BBO algorithms to Proportional Integral Derivative (PID) controller tuning. Derivative free optimisation methods, namely simplex derivative pattern search and implicit filtering are used to hybridize BBO algorithm resulting in improved convergence than original BBO. The effectiveness of the proposed algorithms namely SDPS–BBO, IMF–BBO are demonstrated using PID and Smith predictor controller schemes applied to unit step set point response for a class of dead–time systems and the results are compared with earlier controller tunings proposed by Kookos and Syrcos, Chidambaram, Luyben, Kanthaswamy and Jovitha Jerome.